β3 Adrenergic Receptor Stimulation Promotes Reperfusion in Ischemic Limbs in a Murine Diabetic Model - Bubb, Kristen J.; Ravindran, Dhanya; Cartland, Siân P.; Finemore, Meghan; Clayton, Zoe E.; Tsang, Michael; Tang, Owen; Kavurma, Mary M.; Patel, Sanjay; Figtree, Gemma A. (Frontiers in Pharmacology, 2021)
Aims/Hypothesis: Peripheral arterial disease (PAD) is a major burden, resulting in limb claudication, repeated surgical interventions and amputation. There is an unmet need for improved medical management of PAD that improves quality of life, maintains activities of daily life and reduces complications. Nitric oxide (NO)/redox balance is a key regulator of angiogenesis. We have previously shown beneficial effects of a β3 adrenergic receptor (β3AR) agonist on NO/redox balance. We hypothesized that β3AR stimulation would have therapeutic potential in PAD by promoting limb angiogenesis. Methods: The effect of the β3AR agonist CL 316,243 (1–1,000 nmol/L in vitro, 1 mg/kg/day s. c) was tested in established angiogenesis assays with human endothelial cells and patient-derived endothelial colony forming cells. Post-ischemia reperfusion was determined in streptozotocin and/or high fat diet-induced diabetic and non-diabetic mice in vivo using the hind limb ischemia model. Results: CL 316,243 caused accelerated recovery from hind limb ischemia in non-diabetic and type 1 and 2 diabetic mice. Increased eNOS activity and decreased superoxide generation were detected in hind limb ischemia calf muscle from CL 316, 243 treated mice vs. controls. The protective effect of CL 316,243 in diabetic mice was associated with >50% decreases in eNOS glutathionylation and nitrotyrosine levels. The β3AR agonist directly promoted angiogenesis in endothelial cells in vitro. These pro-angiogenic effects were β3AR and NOS-dependent. Conclusion/Interpretation:β3AR stimulation increased angiogenesis in diabetic ischemic limbs, with demonstrable improvements in NO/redox balance and angiogenesis elicited by a selective agonist. The orally available β3AR agonist, Mirabegron, used for overactive bladder syndrome, makes translation to a clinical trial by repurposing of a β3AR agonist to target PAD immediately feasible.